Depth of cure of 3 Bulk Fill resins composite with different LED curing lamps based on ISO 4049 Standard - Lamas Lara, César Augusto (2023)
Objective: The objective of the research carried out was to compare the depth cure of 3 composite resins using the ISO 4049 standard with 3 different lamp models. Materials and methods: Composite resin cylinders (15 for each experimental group) were made according to ISO 4049 with the following types of resins composites: Beautifil Bulk (BB) (Shofu Inc), Tetric N Ceram Bulk Fill (TC) (Ivoclar Vivadent), Filtek One Restaurador Bulk Fill (FO) (3M ESPE). The composite resins were photoactivated with LED curing lamps. (LED C monowave – Woodpecker, X CURE poliwave - Woodpecker, I LED II poliwave - Woodpecker). Results: The results obtained were analyzed by the Anova test of two factors with a95% of confidence. This was contrasted with Scheffé's multiple comparisons test. The statistical analysis carried out concludes that the 3 Bulk Fill composite resins light-cured with the 3 models of lamps used in this study reached the values indicated by the manufacturers (greater than 4mm). Conclusions: There are significant differences between the lamps used. Being the LED C monowave and the I LED II the ones that obtained the highest values.